Gender Differences in Workplace Humor Among Lecturers: Study on Whatsapp Group(S) - Mirawati, Ira; Suryana, Asep; Hidayat, Mien; Agustin, Herlina (International Journal of Engineering and Technology, 2018)
Humor is an important part of workplace communication. Among lecturers, an online chatting group, such as WhatsApp group, is a scene of humor. As well as real-world humor, gender relations also shape humor in this virtual world. This study investigated gender differences in workplace humor among lecturers on WhatsApp group(s), including the topics, the message forms, and the participantsâ€™ feelings. The subjects were 15 male and 15 female lecturers from three Universities in West Java, Indonesia. The findings of this phenomenology research revealed that humor topic is the first difference. Almost all topics are applicable for male lecturers, and the most frequent ones are their colleague weaknesses, either physical or nonphysical, and sexual content. Female lecturers scarcely initiate humor talk, but they can join it. Being the topic of humor, 73% of female lecturers feel victimized, but only 60% of male lecturers feel the same way. There are 40% male lecturers who feel proud to be the object of humor, because it increases their personal attractiveness and relations as well as their popularity. Female lecturers can freely laugh at her male colleaguesâ€™ weaknesses, but not vice versa.Â Â